Clinical efficacy of transforaminal percutaneous endoscopic lumbar discectomy combined with ozone therapy for the treatment of lumbar disc herniation: comparison with fenestration discectomy. A prospective study // Eficacia clínica de la discectomía lumbar endoscópica percutánea transforaminal, combinada con ozonoterapia, en el tratamiento de la hernia de disco lumbar: comparación con la discectomía por fenestración. Un estudio prospectivo - Zhou, Waiping; Hua, Lei; Li, Mengjie (Investigación Clínica, 2020)
AbstractThe aim of this prospective study was to investigate the clinical efficacy of the transforaminal percutaneous endoscopic lumbar discectomy (PELD), combined with ozone in the treatment of lumbar disc herniation, and to compare its short-term efficacy with fenestration. The study included 109 adult patients admitted to our hospital from January 2015 to December 2016 that met the inclusion criteria. All patients were randomly divided into two groups: the combination group and the fenestration group. The visual analogue scale (VAS) was used to measure postoperative pain of the surgical wound and waist and leg. The JOA score was used to measure recovery status, and the Oswestry disability index (ODI) was used to determine lumbar dysfunction. The operation time and hospitalization time in the combined group were significantly shortened, and the average blood loss and the average amount of intervertebral disc resection were also significantly lower than those in the fenestration group. At all-time points, the VAS score of postoperative pain in the combined group was significantly lower than that in the control group. VAS and ODI scores were significantly decreased and JOA scores were significantly higher in the combined group. The treatment rate in the combined group was significantly higher than that in the open window group. However, there was no a significant difference in the incidence of complications between the two groups. PELD combined with ozone therapy can significantly improve the therapeutic effects and shorten the recovery time of patients with lumbar disc herniation, but does not affect the incidence of postoperative complications.ResumenSe evaluó la eficacia clínica de la discectomía lumbar endoscópica percutánea (PELD) combinada con ozonoterapia en el tratamiento de la hernia de disco lumbar, y se comparó su eficacia a corto plazo con la fenestración. El estudio incluyó a 109 pacientes adultos, divididos aleatoriamente en: un grupo de combinación, en el que los pacientes recibieron PELD y tratamiento con ozono y un grupo tratado mediante fenestración. La escala analógica visual (VAS) se utilizó para medir el dolor postoperatorio de la herida quirúrgica y el de la cintura y la pierna. La escala JOA se usó para medir el estado de recuperación, y el índice de discapacidad de Oswestry (ODI) para determinar la disfunción lumbar. Los tiempos de operación y de hospitalización en el grupo combinado se redujeron significativamente, y los promedios de pérdida de sangre y la cantidad de resección del disco intervertebral también fueron significativamente más bajas que las del grupo de fenestración. La puntuación VAS de dolor postoperatorio en el grupo combinado fue significativamente menor que en el grupo control. Los puntajes VAS y ODI disminuyeron significativamente y los puntajes JOA fueron significativamente más altos en el grupo combinado. La tasa de tratamiento en el grupo combinado fue significativamente mayor que la del grupo de ventana abierta. Sin embargo, no hubo diferencias significativas en la incidencia de complicaciones entre los dos grupos. La PELD combinada con la ozonoterapia puede mejorar significativamente el efecto terapéutico y acortar el tiempo de recuperación de los pacientes con hernia de disco lumbar, pero no afecta la incidencia de complicaciones postoperatorias.